Дослідження ефективності та практичності інструментів для кодогенерації - Денисюк, В. М. (ХНУРЕ, 2024)
Research on the effectiveness and practicality of code generation tools is crucial in modern software development. These tools aim to automate the process of writing code, potentially saving time and reducing human error. This study seeks to evaluate the performance and usefulness of such tools in real-world scenarios.
Keywords: кодогенерація; Text Template Transformation Toolkit